Youth Development Programs Critical Analysis, Rethinking Real Sustainability Measures. Focus on Middle-Eastern and African Contexts. - Salem, Rasha AS (AUC Knowledge Fountain, 2026)
Abstract Using a systematic review of 18 research papers, policy documents, and evaluation reports, the study examines youth development programs sustainability through four aspects. First, the review explores how definitions of marginalized youth are applied in Middle East and African contexts. Furthermore, the review focuses on how programmatic suitability is discussed and implemented through the concepts of localization and contextualization. Additionally, the importance of locally grounded evidence as much as rigorous evidence and finally the implementation tactics. The review uses frameworks of ecological systems theory and empowering management approaches to analyze the data. The findings reveal significant variation in how marginalization is conceptualized—ranging from access gaps and displacement to civic exclusion and intersectionality—and highlight the lack of locally grounded frameworks for assessing suitability. Programs that prioritize contextualization and youth-led localization, and those that employ adaptive management approaches, demonstrate greater sustainability and relevance. However, many programs remain constrained by donor-driven logic models and rigid success indicators, which limit responsiveness to local realities. The thesis calls for a shift toward localized youth programs rooted in community ownership and offers practical recommendations for researchers and practitioners to build conceptual frameworks and to advocate for locally grounded evidence.